1989
DOI: 10.1007/bf00456661
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated nerve corpuscles in the human tympanic membrane

Abstract: Encapsulated nerve endings were found in both the subepidermal connective tissue and the lamina propria of a human tympanic membrane. The structure of the corpuscles was round or oval and contained a number of axon terminals with mitochondria and Schwann cell processes. Amorphous materials were present in the intercellular space. These features appear to be advantageous in transmitting mechanical forces on the capsule to the axon terminals and are comparable to the function of a mechanoreceptor. Resultant chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 4 publications
0
19
1
2
Order By: Relevance
“…The trigeminal nerve and glossopharyngeal nerve are distributed in the tympanic membrane and tympanic cavity membrane, and the tympanic membrane has also been reported to be a pressure receptor [18]. These findings suggest that FEF occurring in middle ear diseases such as exudative otitis media and aviation otitis media is of somatosensory origin; Rask-Andersen et al suggested the mechanoreceptor in the human round window [19].…”
Section: Discussionmentioning
confidence: 94%
“…The trigeminal nerve and glossopharyngeal nerve are distributed in the tympanic membrane and tympanic cavity membrane, and the tympanic membrane has also been reported to be a pressure receptor [18]. These findings suggest that FEF occurring in middle ear diseases such as exudative otitis media and aviation otitis media is of somatosensory origin; Rask-Andersen et al suggested the mechanoreceptor in the human round window [19].…”
Section: Discussionmentioning
confidence: 94%
“…Perhaps more important than passive regulation, the pars flaccida and pars tensa appear to be part of an active regulation system that detects the relative pressure in the middle ear (Rinaldi et al 2013;Eden et al 1990). The tympanic membrane is highly innervated (Lim 1968), and the subepidermal connective tissue and lamina propria of the human tympanic membrane contain mechanoreceptors similar to Pacinian corpuscles that seem to play an important role in sensing pressure (Nagai and Tono 1989). Anatomical evidence that these sensors are involved in active regulation comes from investigations that have shown neural connections between the tympanic plexus, the brainstem, and the Eustachian tube (Hecht et al 1993;Rinaldi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are findings pointing to the presence of a feedback system from the sensory fibers in the ME to the motor fibers of the tubal muscles (Eden et al, 1990;Hecht et al, 1993;Gannon et al, 1994). Moreover, the connection between the sensory receptors in the TM and the tubal function was demonstrated (Nagai and Tono, 1989;, and Esteve (2003) adopted the concept of a neural connection between the sensory receptors in the TM and the tubal muscles.…”
Section: Discussionmentioning
confidence: 92%